Pengaruh Senam Prolanis terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di Puskesmas Raya - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Ginting, Isaharpika Br; Gea, Yosni Handayani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2025)
The World Health Organization American Heart Association in 2015 stated that currently hypertension sufferers in the world have reached around 970 million sufferers, around 330 million are in developed countries and 640 in developing countries. The purpose of this study is to determine the effect of PROLANIS exercise on reducing blood pressure in hypertension sufferers at the Singosari Pematangsiantar Health Center. This study uses a quantitative method. The design of this study uses the Quasi Experiment method with the research design